Exploring the association between organizational justice and job stress among Nigerian correctional staff - Elechi, O. Oko (Journal of ethnicity in criminal justice, 2020)
Organizational justice is important for most employees. Distributive justice (fairness of outcomes) and procedural justice (fairness of processes to reach outcomes) are two major dimensions of organizational justice. Limited research has examined how perceptions of the distributive and the procedural types of justice are linked with job stress of correctional staff, and the vast majority of this limited research has been conducted with U.S. staff. The current study examined how these dimensions of organizational justice are associated with job stress among Nigerian correctional staff. Findings from a survey of 120 staff members from a correctional institution in Southeast Nigeria showed a significant relationship between organizational justice and job stress. Contrary to a similar study in the United States that found that distributive justice had more impact on correctional job stress, employee perceptions that organizational processes and procedures were fair and transparent were associated with a reduced level of stress in Nigeria. One implication of the study findings is that the impact of the distributive and procedural types of justice on staff morale and stress may be attributed more to environmental context and situation.